Synthesis of gold nanoparticles using Sambucus wightiana extract and investigation of its antimicrobial, anti-inflammatory, antioxidant and analgesic activities - Fazli Khuda; Zafar Ul Haq; Ihsan Ilahi; Rahim Ullah; Ayub Khan; Hassan Fouad; Atif Ali Khan Khalil; Zaki Ullah; Muhammad Umar Khayam Sahibzada; Yasar Shah; Muhammad Abbas; Tayyaba Iftikhar; et al. (Arabian Journal of Chemistry, 2021)
Resistance to antimicrobial agents are rendering therapies ineffective around the globe, leading to increased mortality and treatment cost. Likewise, non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics possess several side effects particularly peptic ulcer and gastrointestinal problems. Metallic nanoparticles significantly enhances the therapeutic efficacy of natural extracts owing to improved bioavailability thereby lowering the dose and side effects. The purpose of this research was to investigate the efficacy of gold nanoparticles (AuNPs). In this study, Sambucus wightiana whole plant aqueous extract was used for rapid and eco-friendly synthesis of AuNPs. They were characterized by various analytical techniques including UV–Visible spectroscopy (UV–Vis), transmission and scanning electron microscopy (TEM and SEM), energy dispersive X-ray spectroscopy (EDX), Zetasizer, X-ray diffractometer (XRD) and Fourier transform infra-red spectroscopy (FTIR). The UV–Vis spectra revealed a distinct absorption peak at 539 nm; TEM and SEM images confirmed the formation of heterogeneously dispersed AuNPs with an average area of 152.77 nm2 and width of 15.96 nm. The AuNPs showed significant inhibitory zones against Escherichia coli (25 mm), Staphylococcus epidermis (23 mm) and Salmonella enteritidis (18 mm) with MIC values 0.13, 0.11 and 0.16 mg/ml, respectively. Among fungal strains it showed highest percent inhibition against Fusarium solani (90%) and Microsporum canis (80%) with MIC values 0.02 and 0.01 mg/ml, respectively. It showed maximum anti-inflammatory activity (43.70, 48.80 and 57.08%) at 20 mg/kg dose at both early and late hours of inflammation. Likewise, in vitro models depicted concentration dependent inhibition of 5-LOX and COX-2 enzymes. AuNPs showed highest antioxidant activity (68.7% inhibition) at 1000 µg/ml, compared to ascorbic acid that showed 77.8% inhibition at the same concentration. Similarly, it exhibited significant (P ≤ 0.001) dose dependent analgesic effect with maximum inhibition (56.22%) at 20 mg/kg. In conclusion, the above findings suggest that AuNPs should be studied further in order to develop safe and effective formulations.